دور المسؤولية الاجتماعية في تعزيز استدامة منظمات الاعمال - الشمري، منال ضاهر (جامعة الجلفة, 2022)
تحظى المسؤولية الاجتماعية والتنمية المستدامة باهتمام عالمي كبير وذلك نظير ما تقدمة من نتائج إيجابية للمجتمع ولمنظمة، ويهدف هذا البحث إلى توضيح دور المسؤولية الاجتماعية للمنظمات الأعمال في تحقيق الاستدامة واختبار العلاقة بين المسؤولية الاجتماعية بأبعادها: البعد الاقتصادي والقانوني والخيري والبيئي والاستدامة. ولتحقيق أهداف الدراسة تم اعتماد المنهج الوصفي التحليلي ولجمع بيانات الدراسة تم تصميم الاستبيان وتوزيعه على 83 من موظفين شركة أبار حائل، وتوصلت الدراسة إلى وجود علاقة طردية ذو دلالة إحصائية بين المسؤولية الاجتماعية والاستدامة، وأيضا أنه لا توجد فروق ذات دلالة إحصائية حول دور المسؤولية الاجتماعية في تعزيز الاستدامة للمنظمات تعزى للمتغيرات الديموغرافية التالية: (الجنس، العمر، المستوى التعليمي، الخبرات الوظيفية). Social responsibility and sustainable development are receiving global attention in return for their positive results for society and organization. This research aims to clarify the role of social responsibility for business organizations in achieving sustainability and to test the relationship between social responsibility in its dimensions: the economic, legal, philanthropic, environmental and sustainability dimensions To achieve the objectives of the study, the descriptive analytical approach was adopted, and to collect the study data, a questionnaire was designed and distributed to 83 employees of Abar Hail Company. The study concluded that there is a direct statistically significant relationship between social responsibility and sustainability, and that there are no statistically significant differences about the role of social responsibility in promoting sustainability for organizations due to demographic variables (gender, age, educational level, job experiences).
Keywords: دعائم الاستدامة -- منظمات الأعمال -- التنمية المستدامة -- المسؤولية الاجتماعية